2011
DOI: 10.1271/bbb.110125
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation, Phosphorylation, and Localization of Protein Kinase A ofSchizosaccharomyces pombeupon Glucose Starvation

Abstract: Nine sam mutants that undergo sexual differentiation without requiring starvation in Schizosaccharomyces pombe were previously isolated. In this study, we identified a nonsense mutation on the pka1 locus in the sam6 mutant. pka1 encodes a catalytic subunit of protein kinase A (PKA). Replacement and overexpression of pka1 suppressed the KCl sensitivity and hyper-mating phenotype of sam6, confirming that sam6 is an allele of pka1. To characterize further the regulation of Pka1, we tested the physical interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Both kinases phosphorylate Atg13 at different sites and inhibit, in a different way, the Atg1 complex [24], a key site that integrates different autophagic signals, as indicated also by the above reported effects of Snf1p and Pho85p [22]. In this regard, it is relevant that under glucose deprivation the regulatory and catalytic subunits form the PKA inactive complex [25], because this supports the inhibitory role of glucose on autophagy. Sch9, the closest yeast homologue of mammalian S6K1 and a substrate of TorC1, is also involved in nutrient sensing as an inhibitor of autophagy and in cooperation with PKA [26], although it is apparently less important.…”
Section: Regulation Of Autophagy By Glucose In Yeastmentioning
confidence: 97%
“…Both kinases phosphorylate Atg13 at different sites and inhibit, in a different way, the Atg1 complex [24], a key site that integrates different autophagic signals, as indicated also by the above reported effects of Snf1p and Pho85p [22]. In this regard, it is relevant that under glucose deprivation the regulatory and catalytic subunits form the PKA inactive complex [25], because this supports the inhibitory role of glucose on autophagy. Sch9, the closest yeast homologue of mammalian S6K1 and a substrate of TorC1, is also involved in nutrient sensing as an inhibitor of autophagy and in cooperation with PKA [26], although it is apparently less important.…”
Section: Regulation Of Autophagy By Glucose In Yeastmentioning
confidence: 97%
“…We therefore examined Pka1, a kinase regulated by cAMP. Previous studies reported that Pka1 undergoes inhibitory phosphorylation when cells were starved for glucose for several hours or more (Gupta et al, 2011;McInnis et al, 2010). As shown in Fig.…”
Section: Glucose/camp Signaling Regulates Tf2s Expressionmentioning
confidence: 73%
“…14,29−33) The strains lacking functional components of the cAMP/PKA pathway (cyr1Δ and pka1Δ) were sensitive to 1.5 M KCl but not to 0.3 M NaCl and 2 M sorbitol, as previously shown. 10,13,14,34) The cyr1Δ and pka1Δ strains were found to exhibit a 0.3 M CaCl 2 -sensitive phenotype (Fig. 1).…”
Section: Loss Of Functional Pka Results In Cacl 2 -Sensitive Phenotypementioning
confidence: 98%
“…12) The nuclear-cytoplasmic redistribution of both proteins is triggered by glucose-limitation, KCl stress, and in stationary-phase growth 12) ; and Pka1 physically interacts with Cgs1 under glucoselimited conditions and not under glucose-rich conditions. 13) Pka1 is phosphorylated at threonine 356 under glucose-limited conditions 13,14) and Pka1 phosphorylation is elevated in cyr1Δ mutants and is promoted by KCl. 15) In glucose-rich medium, the non-phosphorylated form of mutant Pka1 (T356A) localizes evenly between the cytoplasm and the nucleus, while the phosphomimetic mutant Pka1 (T356D) concentrates only in the nucleus.…”
mentioning
confidence: 99%